Visual informatics: sustaining research and innovations second International Visual Informatics Conference, IVIC 2011, Selangor, Malaysia, November 9-11, 2011, proceedings, part II - International Visual Informatics Conference Selangor, Malaysia) 2011; Halimah Badioze Zaman 1954-.; SpringerLink (Online service). (Berlin New York Springer, 2011)
The two-volume set LNCS 7066 and LNCS 7067 constitutes the proceedings of the Second International Visual Informatics Conference, IVIC 2011, held in Selangor, Malaysia, during November 9-11, 2011. The 71 revised papers presented were carefully reviewed and selected for inclusion in these proceedings. They are organized in topical sections named computer vision and simulation; virtual image processing and engineering; visual computing; and visualisation and social computing. In addition the first volume contains two keynote speeches in full paper length, and one keynote abstract.
Electronic reproduction.
Keywords: Information visualization -- Congresses; Visualization -- Congresses; Image analysis -- Congresses; Image processing -- Congresses; Optical data processing -- Congresses; Electronic books